The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1988
DOI: 10.1002/tcm.1770080405
|View full text |Cite
|
Sign up to set email alerts
|

Comparative antimutagenicity of chlorophyllin and five other agents against aflatoxin B1‐induced reversion in Salmonella typhimurium strain TA98

Abstract: Chlorophyllin was studied for its antimutagenic activity against aflatoxin B1 in Salmonella typhimurium strain TA98 using the plate-incorporation test in the presence of S9 activation. Comparative antimutagenicity between chlorophyllin and certain commonly studied antimutagens (i.e., vitamins A, C, and E, retinoic acid, and beta-carotene) was also examined. A dose-related inhibition of aflatoxin B1 mutagenicity by chlorophyllin was observed, with the mutagenicity being abolished by 860 nmole chlorophyllin per … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

1992
1992
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…The first studies with CHL in our laboratory used the Salmonella assay, and were based on preliminary experiments which examined the antimutagenic activity of CHL vs. AFB 1 [3]. A key observation in the studies by Whong et al [3] was that the inhibitory activity occurred only when CHL and AFB 1 were incubated concurrently in the assay, suggesting that direct interaction between the inhibitor and mutagen might be important for antimutagenic activity.…”
Section: In Vitro Antimutagenic Activity Of Chl Vs Afb 1 and Afb 1 -mentioning
confidence: 99%
See 1 more Smart Citation
“…The first studies with CHL in our laboratory used the Salmonella assay, and were based on preliminary experiments which examined the antimutagenic activity of CHL vs. AFB 1 [3]. A key observation in the studies by Whong et al [3] was that the inhibitory activity occurred only when CHL and AFB 1 were incubated concurrently in the assay, suggesting that direct interaction between the inhibitor and mutagen might be important for antimutagenic activity.…”
Section: In Vitro Antimutagenic Activity Of Chl Vs Afb 1 and Afb 1 -mentioning
confidence: 99%
“…A key observation in the studies by Whong et al [3] was that the inhibitory activity occurred only when CHL and AFB 1 were incubated concurrently in the assay, suggesting that direct interaction between the inhibitor and mutagen might be important for antimutagenic activity. We observed the antimutagenic activity of CHL vs. AFB 1 using trout liver microsomes as the source of metabolic activation [4], but showed the inhibitor to be more effective against the direct-acting mutagen AFB 1 -8,9-epoxide (Fig.…”
Section: In Vitro Antimutagenic Activity Of Chl Vs Afb 1 and Afb 1 -mentioning
confidence: 99%
“…However, very soon afterwards most research on the matter was focused on the effect of chlorophyllin (CHL) (Figure 4), mostly because this chemical is a water-soluble, sodium and copper salt, chlorophyll derivative. In regard to its protective effect on AFB1 damage, one of the first studies with CHL was made by quantifying the number of revertants of specific base-pair mutants in Neurospora crassa (Whong et al, 1988). The study showed strong inhibition of the antimutagen on the AFB1-mutagenicity determined in growing cultures of the mold, a result which prompted the group to continue their studies but now in Salmonella typhimuriun, strain TA98, as a model (Whong et al, 1988).…”
Section: Chlorophyllinmentioning
confidence: 99%
“…In regard to its protective effect on AFB1 damage, one of the first studies with CHL was made by quantifying the number of revertants of specific base-pair mutants in Neurospora crassa (Whong et al, 1988). The study showed strong inhibition of the antimutagen on the AFB1-mutagenicity determined in growing cultures of the mold, a result which prompted the group to continue their studies but now in Salmonella typhimuriun, strain TA98, as a model (Whong et al, 1988). The authors used the plateincorporation test in this bacteria and found a concentration-dependent inhibition of AFB1 mutagenicity when the cells were treated with the tested substances, concurrently; in their assay they observed that 860 nmol/plate of CHL completely abolished the mutagenicity of the toxin.…”
Section: Chlorophyllinmentioning
confidence: 99%
“…Chlorophyllin (CHL) is a sodium-copper salt of chlorophyll that exhibits antimutagenic activity in several shortterm genotoxicity assays [Katoh et al, 1983;Tenvel and van der Hoeven, 1985;Ong et al, 1986;Whong et al, 1988;Negishi et al, 1989;Dashwood et al, 1991;Warner et al, 1991;Tachino et al, 19941. Studies in vitro indicate that CHL acts via multiple mechanisms, including the following: 1) inhibition of mutagen activation, 2) degradation of electrophilic ultimate carcinogens [Tachino et al, 19941, and 3) molecular complex formation with the promutagen [Negishi et al, 1989;Dashwood and Guo, 1992;Breinholt et al, 1995al.…”
Section: Introductionmentioning
confidence: 99%